Complementary roles of the Cek1 and Cek2 MAP kinases in Candida albicans cell-wall biogenesis. (January 2016) - Correia, Inês; Román, Elvira; Prieto, Daniel; Eisman, Blanca; Pla, Jesús
Aims: To investigate whether Cek2 (as Cek1) is involved in the biogenesis of the fungal cell wall and to uncover differences and similitudes between both proteins.Materials & methods: We used molecular genetics to characterize the role of Cek2 in MTL-heterozygous cells.Results: Deletion of CEK2 (similar to CEK1 ) renders cells sensitive to cell-wall-interfering drugs and, when overexpressed, Cek2 can become phosphorylated upon the same stimuli that activate Cek1. This is dependent on elements of the sterile–vegetative growth (SVG) pathway. Cek2, contrary to Cek1, mediates a transcriptional activity in a C. albicans -adapted two-hybrid system that is essential for Cek1–Cek2 interaction.Conclusion: Cek2 has a cryptic role in cell-wall biogenesis and its role is not entirely redundant to Cek1.